PERKEMBANGAN MODERNISASI SISTEM PENDIDIKAN ISLAM DI INDONESIA MELALUI GAGASAN ISLAMISASI ILMU PENGETAHUAN. - TAUFIK RIZKI SISTA (Jurnal Ilmiah Pesantren, 2019)
The advance of modern science and technology entered the Islamic world, especially after the opening of the nineteenth century AD, which in Islamic history was known as the beginning of the Modern Period. Modernization of education in Indonesia is better known as reformation. The emergence of the dichotomy according to the experts is a decline of science that eventually led to the intellectuals who mastered science in an uncomprehensive manner.This paper is the result of literature research investigated by library document searching method. Primary sources used are the results of writings published in journals with the theme of education and Islamization of science, while the secondary source is a book of books with related themes.The purpose of this paper is (1) To know how the concept of modernization of education comprehensively, (2) to know the idea of Islamization of Science in the modernization of education, (3) to know the development of modernization of Islamic education system through Islamization of Science in Indonesia.The results of this paper can be concluded that to the modern education system there are two ways that are needed if the birth of an integrated pattern of education is desired. The first is the effort to integrate science and religious knowledge, while the second is to integrate leader characteristics and managerial characteristics within formal education organizations.